Perception of ‘patient safety culture’ among healthcare professionals in the field of haematopoietic stem cell transplantation and CAR-T therapy: a multicentre cross-sectional observational study by Italian Transplant Group for Bone Marrow Transplantation, Haematopoietic Stem Cells and Cell Therapy (GITMO) - Giuseppe Vetrugno; Massimo Martino; Chiara Visintini; Vincenzo M Grassi; Marco Cioce; Angela Iula; Patrizia Cornacchione; Stefano Botti; Valentina Zoboli; Raffaella Cerretti; Sonia Soave; Barbara Guidi; et al. (BMJ Open Quality)
Adverse events associated with healthcare services in hospitalised patients represent a growing burden, generating significant costs for individuals, healthcare facilities and society. Their clinical and economic impact is particularly critical in the context of haematopoietic stem cell transplantation (HSCT) and chimeric antigen receptor (CAR)-T therapy. A positive safety culture is widely recognised as a crucial factor in reducing hospital errors. This study aimed to evaluate the perception of ‘Patient Safety Culture’ (PSC) among professionals working in the HSCT and CAR-T therapy fields.A multicentre, cross-sectional observational study was conducted by GITMO. The sample included healthcare professionals (physicians, nurses and others) who had been part of the Transplant Programme for at least 2 years. To assess PSC perception, the validated Italian version of the Hospital Survey on Patient Safety (SOPS V.2.0) from the Agency for Healthcare Research and Quality was used.The survey was completed by 166 professionals from 47 centres (54% participation rate). Binary logistic regression showed that haematologists reported higher PSC perceptions compared with nurses with positive responses exceeding 75%, particularly in dimensions such as ‘Teamwork’ (nurse OR=0.306, p=0.009), ‘Organizational Learning—Continuous Improvement’ (nurse OR=0.332, p=0.011), ‘Response to Error’ (nurse OR=0.360, p=0.024), ‘Supervisor Support’ (nurse OR=0.160, p<0.001), ‘Communication About Error’ (nurse OR=0.152, p=0.001) and ‘Global Instrument’ (nurse OR=0.150, p<0.001).The findings highlight the need for targeted interventions to address discrepancies in PSC perceptions across professional roles, age groups and regions. Enhancing staffing levels and promoting the use of incident reporting systems are critical strategies to strengthen safety culture in HSCT and CAR-T therapy settings.